2020
DOI: 10.26434/chemrxiv.11831103.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of the SARS-CoV-2 (2019-nCoV) 3C-like Protease (3CLpro) Structure: Virtual Screening Reveals Velpatasvir, Ledipasvir, and Other Drug Repurposing Candidates

Abstract: We prepared the three-dimensional model of the SARS-CoV-2 (aka 2019-nCoV) 3C-like protease (3CL ) using the crystal structure of the highly similar (96% identity) ortholog from the SARS-CoV. All residues involved in the catalysis, substrate binding and dimerisation are 100% conserved. Comparison of the polyprotein PP1AB sequences showed 86% identity. The 3C-like cleavage sites on the coronaviral polyproteins are highly conserved. Based on the near-identical substrate specificities and high sequence identities,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 7 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…The analysis of the trajectories showed that eluxadoline, which has been recently approved to be used in the treatment of Irritable Bowel Syndrome with diarrhea 92 Another compound identified in this study was diosmin, and like eluxadoline, it has been proposed as a candidate molecule in the treatment of SARS-CoV-2 in a couple of recent in silico studies 8, 93,94 . It is also important to emphasize that diosmin has been currently tested to be used in a combinatorial therapy with hesperidin for prophylaxis and treatment of COVID-19 95 .…”
Section: Clustering Of Trajectories Pertaining To Apo M-pro Revealed mentioning
confidence: 66%
“…The analysis of the trajectories showed that eluxadoline, which has been recently approved to be used in the treatment of Irritable Bowel Syndrome with diarrhea 92 Another compound identified in this study was diosmin, and like eluxadoline, it has been proposed as a candidate molecule in the treatment of SARS-CoV-2 in a couple of recent in silico studies 8, 93,94 . It is also important to emphasize that diosmin has been currently tested to be used in a combinatorial therapy with hesperidin for prophylaxis and treatment of COVID-19 95 .…”
Section: Clustering Of Trajectories Pertaining To Apo M-pro Revealed mentioning
confidence: 66%
“…The close similarity of the replication mechanism in the Hepatitis C virus and SARS-CoV-2 makes it an interesting therapeutic option for drug development. Recently, it was reported to interact with 3C like protease (3CLpro) of COVID-19 27 . Flavin adenine dinucleotide also depicted to have binding energy to be higher than the threshold (Figure 3 and Supplementary Information, Table S4).…”
Section: Docking Analysis Revealed the Interaction Of Top Hits With Tmentioning
confidence: 99%
“…Repurposing drugs is a much quicker endeavor than discovering new ones since their chemical optimization, toxicology profiling, clinical trials and bulk manufacturing are already in place [1]. Several research groups have already proposed possible candidates for testing [2][3][4][5][6][7]. The results of this testing could provide a spectrum of outcomes -ranging from a compound that show high promise for use in patient treatment to very little activity.…”
Section: Introductionmentioning
confidence: 99%